(untitled) (FULafia Journal of Science and Technology, 2018)
An ethno-medicinal survey was carried out in October, 2017 to collate information on the medicinal plants used by the Chawai people of Kauru Local Government Area of Kaduna State.A 10m x 10m quadrat size was used to sample 8 plots, 200 metres apart. Oral interviews were conducted with Elders, Alternative Medicinal Practitioners, Hunters and women. Seventy-two (62) plant species were recorded and distributed across 31 families out of which 68 were used for alternative medicinal purposes and distributed according to the following families:Mimosoideae (12.90%),Anacardiaceae (9.68%), Caesalpinodeae (8.06%), Euphorbiaceae (8.06%), while Apocynaceae, Moraceae, Fabaceae and Rubiaceae showed (4.84%) each. The study revealed that the plant part mostly used are the roots when compared to the other parts of the plant (barks, leaves, stems, roots, fruits, seeds,latex and flowers). Latex and flowers were amongst the least parts used. There is the urgent need for more documentation of the traditional ethno-medicinal knowledge.